PENGARUH BEBAN KERJA DAN ROLE CLARITY TERHADAP KINERJA PEGAWAI MELALUI KOMITMEN KERJA PADA BADAN PENGELOLAAN KEUANGAN DAN PENDAPATAN DAERAH KABUPATEN PASURUAN - Priyanto, Rudi; Sundjoto; Sri Rahayu (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of workload and role clarity on employee performance and work commitment at the Financial and Regional Revenue Management Agency of Pasuruan Regency. Using a sample of 100 employees, the data were analyzed using the Partial Least Square (PLS) approach and SmartPLS 3.0 software. The results show that: (1) Workload positively affects employee performance, (2) Workload positively affects work commitment, (3) Role clarity positively affects employee performance, (4) Role clarity positively affects work commitment, (5) Work commitment positively affects employee performance, (6) Workload affects employee performance through work commitment, and (7) Role clarity affects employee performance through work commitment. These findings confirm that effective management of workload and clear role definitions can enhance employee performance through increased work commitment.